2020
DOI: 10.1111/jgh.14927
|View full text |Cite|
|
Sign up to set email alerts
|

Dengue hepatitis with acute liver failure: Clinical, biochemical, histopathological characteristics and predictors of outcome

Abstract: BackgroundHepatitis infection from non‐hepatotropic viruses such as dengue virus (DENV) is increasing worldwide. There is increasing recognition of the changing epidemiology and atypical presentations of DENV infection including acute liver failure (ALF). There is paucity of data regarding incidence, disease characteristics, and markers of prognosis in patients who develop DENV‐related ALF.MethodsWe aimed to study the incidence, clinical features, laboratory characteristics, and determinants of outcome in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…In the liver, DENV infection occurred in hepatocytes and Kupffer cells but not in endothelial cells. Other studies reported the same pathological findings[ 34 , 38 , 39 ]. Recently, Win and colleagues reported that the prominent findings of the ultrastructure features of human liver specimens from patients who died of DHF were extensive cellular damage and steatosis.…”
Section: Dengue Hemorrhagic Fever and Liver Involvementsupporting
confidence: 75%
See 2 more Smart Citations
“…In the liver, DENV infection occurred in hepatocytes and Kupffer cells but not in endothelial cells. Other studies reported the same pathological findings[ 34 , 38 , 39 ]. Recently, Win and colleagues reported that the prominent findings of the ultrastructure features of human liver specimens from patients who died of DHF were extensive cellular damage and steatosis.…”
Section: Dengue Hemorrhagic Fever and Liver Involvementsupporting
confidence: 75%
“…Mean AST and ALT concentrations ranged from 2-fold to 5-fold rises, which demonstrated mild hepatitis with self-limited. The 10-fold elevation of AST and ALT was reported in 4%-15% of the patients associated with SDD and may deteriorate to be ALF[ 33 , 34 ]. The physical sign of hepatomegaly with hepatic tenderness did not predict the rising of AST and ALT[ 16 ].…”
Section: Dengue Hemorrhagic Fever and Liver Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…With a cut-off ≥ 15 points, the MELD score could predict ALF from DISH with an excellent performance (AUROC of 0.906, 88.2% sensitivity and 87.3% specificity). Overall, we suggest that the liver background and functional reserve after dengue infection are the main prognostic factors and have a stronger influence on the development of ALF than the severity of liver insults from the virus[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, many cases of denguerelated ALF were observed in both children and adults during the Indian seasonal epidemic, including cases of mixed infections. 70 In an Indian study, dengue hepatitis progressed to ALF in 0.35%. 71 The mean age of dengue-related ALF was 29 years.…”
Section: Other Viruses Including Dengue Virusmentioning
confidence: 99%